The Influence of Leadership Style, Organizational Culture and Communication on Employee Performance at PT Ukindo Blankahan Mill Regency - Prisscilla Nova Silaen; M. Chaerul Rizky (International Journal of Society and Law, 2024)
This study aims to analyze the influence of leadership style, organizational culture, and communication on employee performance at PT Ukindo Blankahan Mill, Langkat Regency, North Sumatra. A quantitative approach with a survey method is used to collect data from a sample of employees in the company. The research sample was determined through a saturated sample technique, and data was collected using questionnaires that had been tested for validity and reliability. Data analysis was carried out using multiple linear regression to determine the influence of each independent variable on the dependent variable using SPSS version 25 data processing tools. The results of the study show that leadership style has a positive and significant influence on employee performance, which means that effective leaders can increase productivity and work efficiency. Organizational culture has also been found to have a significant effect on performance, suggesting that the values and norms applied in the organization can increase employee motivation and engagement. Communication, as the last variable, does not have a positive and significant influence on employee performance. Simultaneously, the variables of leadership style, organizational culture, and communication have a positive and significant influence on employee performance at PT UKINDO.